Pengaruh Model Guided Inquiry dan Problem-Based Learning terhadap Pemahaman Konsep Siswa - Elvara Norma Aroyandini; Muhammad Nilzam Aly; Nur Hamid; Annisa Firanti; Dwi Muhidin Pahlefi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
This study aims to determine the influence of the guided inquiry model and problem-based learning on the conceptual understanding of class VII A and VII K students of State Tsanawiyah Madrasa (MTs N) 3 Sragen on environmental pollution material. This research is a quasi-experimental research with a non equivalent control group design. After being treated with the guided inquiry model, the average of students' learning outcomes was 89.5, while the problem-based learning model was 88.3. To prove that there is an effect of the two models on students' conceptual understanding, a paired sample t-test was conducted, in which the two classes showed a significance <0.05 so that H1 was accepted or H0 was rejected. Its means that the two models influence students' conceptual understanding of environmental pollution material. The guided inquiry model in this study has a higher impact than problem-based learning. These results are also supported by the N-Gain score on the guided inquiry model, which is higher than the problem-based learning model with scores of 0.67 and 0.53, respectively. Both N-Gain scores are in the “medium” improvement category.